Digital Resource Management and User Services in Central University Libraries of Western India: A Review (International Journal of Food and Nutritional Sciences, 2022)
This review examines the management of digital resources and user services in central university libraries across western India. Central university libraries play a crucial role in facilitating access to scholarly information through their digital resources and services. The study investigates current practices, challenges, and advancements in digital resource management, encompassing e-books, online databases, and institutional repositories. It also assesses user-centric services such as digital literacy programs, remote access facilities, and user support mechanisms. Key issues explored include infrastructure capabilities, funding constraints, and user satisfaction levels. The review synthesizes recent literature and empirical studies to provide insights into strategies for enhancing digital resource management and user services in the context of central university libraries in western India. This examination aims to contribute to the optimization of library services and the enrichment of academic research and learning experiences in the region.